Effective improvement of D-phenylglycine aminotransferase solubility by protein crystal contact engineering - Aiya Chantarasiri (2018)
Structure-guided genetic engineering of D-phenylglycine aminotransferase (D-PhgAT) aimed at increasing protein solubility was attempted. In silico analyses predicted the Asn439 and Gln444 as highly solvent-exposed β-turn residues involved with protein crystal contact (CC) potential candidates for solubility-improving mutations. They were replaced with Asp and Glu creating the N439D and Q444E single mutants, and N439D/Q444E double mutant with 2.5-, 3.3-and 5.9-fold increases in solubility, respectively. The protein CC prevention effect rather than the net charge effect accounted for the dramatically improved solubility since the N439D, Q444E and N439D/Q444E mutations altered the isoelectric point of D-PhgAT by only 0.1, 0.1 and 0.3 units, respectively. Examination of the D-PhgAT structural model revealed that the N439D mutation weakened the CC attraction force and the Q444E mutation created electrostatic repulsion at the CC point. Analysis of circular dichroism spectra, melting temperature, and D-PhgAT-specific activity showed that the mutations posed no unfavorable effect on the conformational stability and catalytic performance of the enzyme. The protein solubility-improving strategy employed on D-PhgAT in this study was successful with minimal protein structure modification required. It should be applicable with a high chance of success for other proteins, especially those with 3-D structural models available. Copyright © 2012 S. Karger AG, Basel.